Designing a smart city in Kuwait: an initial study - Alkandari, Abdulrahman; Alshaikhli, Imad Fakhri Taha (Design for Scientific Renaissance, 2012)
This paper will discuss different humanity and environmental problems that face the Kuwait city, such problems are slowing down the wheel of development in the country. Much of these problems and challenges can be solved by building a smart infrastructure based on wireless sensor network (WSN) that will be connected with backbone system depending on global network in various aspects: GSM, 4G, GPS, GIS, WIFI, WIMAX, and Cloud computing. This solution will create a city of intelligence which can be controlled automatically through sensors. Some of the sensors will be portable and carried by humans (Bracelet) or vehicles (Tag) while carrying necessary information in memory storage which can read/write into/from the sensors. Furthermore, other sensors can be fixed at important places while transmitting and receiving data. Recently, most of the researchers and IT companies proposed the idea of smart cities while focusing on a certain problem inside the city and giving a smart solution to that problem. For example, smart grid, smart meter, smart healthcare, traffic management system, smart energy, and smart Building. The idea behind this paper is to solve different city issues by using WSN and building an initial smart infrastructure using Kuwait city as case study.